2016
DOI: 10.1159/000447432
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Volume Index Associates with a Decreased Risk of Prostate Cancer: Results of a Large Cohort of Patients Elected to a First Biopsy Set

Abstract: Background/Aims/Objectives: In patients elected to the first prostate biopsy set, the risk of prostate cancer (PCA) may be predicted by clinical factors. The aim of this study was to investigate on prostate volume index (PVI), defined as the ratio of volume of the transitional zone to the volume of the peripheral zone, and PCA risk. Methods: The study retrospectively evaluated 1,327 patients and included only the first biopsy set with 14 cores. PCA risk was assessed by using the multivariate logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…This is in line with a recent TRUS volumetry investigation of 596 cases [11] . With increasing prostate volume, specific areas may be underrepresented on systematic sampling such as lesions located anteriorly and in the apex or missed by targeted biopsies, although there is no data for targeted biopsies.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with a recent TRUS volumetry investigation of 596 cases [11] . With increasing prostate volume, specific areas may be underrepresented on systematic sampling such as lesions located anteriorly and in the apex or missed by targeted biopsies, although there is no data for targeted biopsies.…”
Section: Discussionsupporting
confidence: 91%
“…NPC was independently decreased by PVI indicating inverse association between PVI and tumor load. This finding was expected since we have previously shown that PVI associated with a decreased risk of PCA at baseline biopsies ( 7 , 13 , 14 ). So far, PVI associated with a decreased risk of PCA and decreased NPC in patients undergoing baseline biopsies indicating inverse association with tumor biology.…”
Section: Discussionsupporting
confidence: 67%
“…PVI is a pure measure since represents a ratio between volumes. We have shown that PVI represents the gradient of the regression line of TZV as a function of PZV ( 7 , 13 , 14 ). Considering the relations between PZV and TZV, PVI quartiles represent the different gradients of the regression lines between the two volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that small prostates have larger volumes of the peripheral zone and are more likely to develop more aggressive cancers; moreover, large prostates show thin peripheral zone volumes as well as sampling errors and then less likely to develop high-grade cancers. Literature investigation support this hypothesis since it has been shown that the ratio between the volume of the central zone and the volume of the peripheral have an impact on the risk of having a positive biopsy [26,27] . Our study showed that prostates having more than one BPC were more likely to have DR/P.…”
Section: Discussionmentioning
confidence: 88%